Multimodal ultrasonography in the diagnosis and treatment of chronic thyrotoxic myopathy: a prospective study - Wang, Roumei; Huang, Rui; Fu, Shien; Tang, Yunxia; Liu, Yaoli (Frontiers in Endocrinology, 2025)
ObjectiveThis study integrates high-frequency ultrasonography with shear wave elastography (SWE) to perform a multimodal quantitative assessment of the rectus femoris and thyroid tissue architecture in patients with chronic thyrotoxic myopathy (CTM). A novel predictive model for CTM progression was developed by quantitatively assessing biomechanical parameters, including muscle and thyroid parenchymal stiffness, providing an objective imaging-based foundation for early disease intervention.MethodsThis prospective study enrolled 75 patients with hyperthyroidism and 53 healthy controls. The biomechanical parameters of the rectus femoris and thyroid tissue were quantitatively assessed using SWE. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the predictive efficacy of rectus femoris and thyroid tissue elasticity parameters for CTM diagnosis. A multivariate logistic regression model was developed to investigate the association between muscle stiffness, thyroid stiffness, and CTM risk. Additionally, patients with CTM received pharmacotherapeutic interventions, and clinical indexes were systematically monitored along with dynamic changes in thyroid and rectus femoris correlation parameters before and after treatment to evaluate therapeutic efficacy.ResultsThe CTM group exhibited a significantly lower mean Young’s modulus (E-mean) of the rectus femoris than the non-CTM and healthy groups (p < 0.01). In contrast, the CTM group had a significantly higher thyroid E-mean than the other groups (p < 0.01). Moreover, the rectus femoris E-mean was positively correlated with grip strength (r = 0.437, p < 0.01) and lower limb fatigue test (r = 0.247, p = 0.042) in patients with CTM. ROC curve analysis revealed that the combined diagnostic approach achieved the highest sensitivity and specificity for CTM, with an area under the curve of 92.5%. A multivariate logistic regression model revealed that, after adjusting for confounding factors, rectus femoris E-mean and thyroid E-mean were significant predictors of CTM. Following treatment with antihyperthyroid drugs, significant improvements were observed in thyroid hormone levels, upper and lower limb muscle function tests, and muscle-related parameters compared with their pretreatment levels, with all differences reaching statistical significance (p < 0.01).ConclusionBy quantitatively assessing the morphological and biomechanical characteristics of the rectus femoris and thyroid gland, multimodal ultrasonography can provide a reliable imaging basis for the early prediction and therapeutic monitoring of CTM.